Psycholinguistic Analysis Of English Spelling Errors In Indonesian Fifth-Grade Students At SD ‘Aisyiyah 1 Kauman Pagaralam - Amelia Dwi Putri; Yoga Pratama; Umi Kalsum (Journal of Literature Language and Academic Studies, 2026)
Purpose – This study aims to identify the types of English spelling errors and analyze the underlying psycholinguistic factors causing these errors among fifth-grade students at SD ‘Aisyiyah 1 Kauman Pagaralam. Methodology – Employing a quantitative descriptive research design, this research involved a saturated sample of 41 students. Data were systematically collected using an English spelling test, including dictation and written tasks, alongside a Likert-scale questionnaire based on the Dual-Route Model (DRM). The collected data were processed utilizing SPSS for descriptive statistical analysis. Findings – The most frequent spelling error was Capitalization Visual (14.3%), followed by Substitution Phonological Auditory (13.7%) and Morphological Visual (12.6%). From a psycholinguistic perspective, these errors were primarily triggered by working memory limitations (Performance mean = 24.05), lexical retrieval failure (Cognitive mean = 22.54), and profound mother tongue interference (L1 mean = 22.51) combined with weak English phonological awareness. Novelty – The study empirically links written spelling error patterns back to their probable psycholinguistic causes in early EFL learners, addressing the research gap of merely counting error frequencies in local contexts. Significance – Educators and curriculum designers would benefit from this study to design targeted pedagogical interventions, ultimately improving transcription skills and writing self-efficacy in Indonesian elementary schools